The Kings Score refines prognostic prediction in hepatocellular carcinoma: a novel application. (11th May 2015) - Pinato, David J.; Karamanakos, Georgios; Ishizuka, Mitsuru; Smirne, Carlo; Pirisi, Mario; Kubota, Keiichi; Sharma, Rohini
Abstract Background & Aims There are a number of prognostic scores in hepatocellular carcinoma (HCC), none of which is optimal in predicting overall survival (OS) in the individual patient, particularly in intermediate stage disease, where patients are not surgically treatable but may qualify for a wide range of palliative interventions. We evaluated the prognostic role of a biochemical algorithm, the Kings Score (KS), in the palliative setting of care. Methods We used the algorithm [age x AST x INR]/platelet count to derive the KS. Full clinical data including Barcelona Clinic Liver Cancer (BCLC) stage were studied in a training set of 97 patients from the UK. Independent predictors of survival identified in multivariate analysis were validated in an independent cohort of 766 patients from Japan and Italy. Results In both training and validation sets, KS was confirmed as an independent predictor of OS (P < 0.01). Ad‐hoc subgroup analysis revealed the KS to be prognostic in the palliative setting, being able to subclassify patients presenting with intermediate and advanced disease according to BCLC criteria (P < 0.001). Conclusion The KS integrates into the BCLC system to improve prognostic substratification in the palliative setting of care. The KS may help reducing disease heterogeneity and refine treatment allocation in intermediate‐advanced HCC.